CCAFS evidence on scalable CSA business models drove USD 170million national policy investment in India to curb crop residue burning - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
Science-based evidence generated by CCAFS-CIMMYT & partners in the CSVs helped the Indian Government to prioritize crop residues management solutions and establish a large scale routing investment of INR 1150 crores for in-situ management using the Happy Seeder technology. Responding the Prime Ministers call to curb to crop residue burning while providing sustainable and scalable solutions, this scheme targets an increased incomes for over 2 million farmers, improving soil health, reducing water use and carbon footprints in 4 million hectares.